Use of E-Resources in the e-ShodhSindhu Consortium: A Study of North Bengal University Library Users - Kumar Mistri, Shubhrangshu (Journal of Information and Knowledge, 2018)
The e-ShodhSindu is the Consortia for Higher Education E-Resources merging three consortia, i.e. UGC-INFONET Digital Library Consortium, INDEST-AICTE Consortium and N-LIST. The e-ShodhSindhu is intended to provide current and archival access to E-Resources i.e. e-books, e-journals, e-journal archives, online databases to its member institutions at a negotiated rate of subscription. This paper studies the use of e-resources in the e-ShodhSindhu Consortium by the North Bengal University Library users. 150 questionnaires were distributed among the faculty members and research scholars. Out of which, 110 filled-in questionnaires were returned. The study reveals that most of the respondents are satisfied with e-resources available in the e-ShodhSindhu Consortium.